Group and Interaction Effects with "No Child Left Behind": Gender and Reading in a Poor, Appalachian District - Bickel, Robert; Maynard, A. Stan (Education Policy Analysis Archives, 2004)
Critics of “No Child Left Behind” judge that it oversimplifies the influence of social context and the place of socially ascribed traits, such as social class, race, and gender, in determining achievement. We hold that this is especially likely to be true with regard to gender-related group effects and gender-implicated interaction effects. We make our concerns concrete in a multilevel, repeated measures analysis of reading achievement in a poor, rural school district located in the southern coalfields of Appalachian West Virginia. Our results suggest that as the percentage of students who are male increases, school mean scores in reading achievement decline for three reasons: individual males do less well than females; the greater the percentage of males, the lower the scores for all students; added to that, the greater the percentage of males, the lower the scores for males specifically. Given the accountability measures and sanctions proposed by “No Child Left Behind,” having a large percentage of males in a school could be disastrous. We conclude that gender effects in reading achievement are complex, easily overlooked, and have no obvious remedy. As such, they lend credence to the view that “No Child Left Behind” oversimplifies the social context of schooling and underestimates the importance of social ascription.